Institutional investors' role in diversifying orientation decision across Tunisian companies - Manel Gharbi; Anis Jarboui (Cogent Economics & Finance, 2017)
The present work's major objective consists in examining the impact of institutional investors' presence on corporate diversification decision. For this sake, a theoretical framework based on the corporate governance contractual approach has been advanced highlighting the idea that the presence of institutional enjoys a diversification-oriented strategic decision. For this purpose, a model is used and applied to Tunisian firms' sample observed over the period 2011-2013. In fact, the study maintains that the presence of institutional investors helps in directly influencing corporate strategic decisions. The reached results, conducted on a sample of 111 Tunisian commercial companies and service-providing firms, appear to reveal the persistence of a significant impact of the institutional investors on diversification decision.
Keywords: 330; governance; ownership concentration; institutional investors; diversification